'A Great Reformatory': Social Planning and Strategic Resettlement in Late Colonial Kenya and Algeria, 1952–63. (January 2017) - Feichtinger, Moritz
In the midst of their bitterly fought wars against anti-colonial guerrilla movements in Kenya and Algeria, British and French colonial authorities launched huge rural development programs. These plans were grounded on the effects of an extremely violent military practice: forced relocation of huge parts of the rural populations into strategic villages. Up to 2.5 million Algerians and 1.2 million Kenyans were affected by strategic resettlement, resulting in humanitarian crisis in both cases. The plans for socio-economic development and the military strategy of forced resettlement cannot be analysed separately. The implementation of socio-economic reforms in such a short time-span and to such an extent required the instruments of power of military force and the disciplinary spatial structure of the strategic villages. Mass relocations of civilians and its effects on the other hand were repeatedly justified with reference to the overall plans for socio-economic development and modernization.